Correlation between Demographic Characteristics and Safety Attitude of Workers in a Dairy Company - Gholamabbas Shiali; Emel Saki; Atefeh Siahi Ahangar (تحقیقات سلامت در جامعه, 2020)
Introduction and purpose: Occupational hazards in the workplace cause serious injuries to workers and create many problems for them. The assessment of workerschr('39') safety attitudes and implementation of codified safety training can reduce accidents, unsafe practices, human errors, and costs. Therefore, the present study aimed to investigate the correlation between the demographic characteristics of individuals and the safety attitude towards work in the workers of a dairy company. Methods: This descriptive study was conducted on all 168 employees working in a dairy companychr('39')s production line. The data collection tool was a two-part questionnaire, and the obtained data were analyzed in SPSS software (version 21). Results: As evidenced by the obtained results, most workers had a positive attitude toward safety (6.7±80.18). There was a significant relationship between the number of occupational accidents and the level of workerschr('39') safety attitude (P=0.01). Moreover, the results pointed to the significant relationship between the number of occupational accidents and the work experience of workers (P=0.004) and the number of occupational accidents and job satisfaction (P=0.044). Conclusion: The assessment of safety attitudes and its dimensions can be of great help to identify those areas of training that require more attention and better design. Prioritizing safety and improving workerschr('39') safety attitudes can reduce occupational accidents in the industry.